Empirical investigation on satisfaction and service quality level of radical process change implementation - Ahmad, Hartini; Francis, Arthur (Universiti Utara Malaysia, 2006)
The paper reviews the literature related to the implementation of radical process changes in higher education (HE) environment. Several issues and implementation results related to radical process change in HEIs, particularly business process reengineering (BPR), are being investigated. Furthermore, as the implementation of process change would have an impact in HEIs,specifically on service quality and customer satisfaction, this paper discusses both concepts. A survey has been developed to assess the students’ satisfaction of the radical process change implemented in one of the HEIs, namely HEI-A which was selected as a case study. The results indicate some significant differences among groups for both satisfaction and service quality measured.The paper provides a framework for future research to develop a metric for measuring satisfaction and service quality level in HEIs. This research contributes to studies of BPR in HE context, by focusing on the key processes performance.